Effect of target-distance training in terms of centrifugal force on some biomechanical variables and 400m hurdles performance under 20 years old - Ahmed Nayef Batoli (Jurnal Porkes, 2026)
The policy to reduce physical education classes from two to one hour per week in Wasit Province, Iraq, coupled with weak administrative support from school principals, poses a serious challenge for physical education teachers. However, there is currently no empirical evidence examining the role of school principals in facilitating physical education instruction following this policy. This study aims to uncover the reality of the principal’s role, identify differences in perceptions based on school accreditation, analyze the relationship between teachers’ years of service and their perceptions of support, and identify the dominant barriers faced by teachers. The study employs a quantitative approach using a descriptive-analytical and comparative-correlational survey design. A purposive sample of 115 physical education teachers from the city center of Kut, Wasit, was selected. The instrument consisted of a 5-point Likert scale questionnaire with content validity (CVI = 0.88) and reliability (Cronbach’s alpha = 0.91). Data analysis utilized descriptive statistics, independent t-tests, and Pearson’s correlation. The role of the principal was classified as low (mean = 2.33). There was a significant difference in perceptions between A-accredited and non-A-accredited schools (t = 2.87; p = 0.005). A moderate negative correlation was found between years of service and perceived support (r = -0.342; p < 0.001). The dominant barriers were: lack of external cooperation (1.72), lack of funding (1.76), and the use of physical education time for other activities (3.29). These findings are linked to transformational leadership theory and occupational socialization theory. School principals fell short on all four dimensions of transformational leadership. Senior teachers have more negative perceptions due to accumulated experience and burnout. Principal support for physical education at Wasit is very low. A policy review, minimum budget allocation, principal training, and revision of accreditation instruments are needed.